Sistem Pengukuran Detak Jantung Janin Melalui Elektrokardiogram Abdominal dan Android - Yusuf Anggara Aji; Nuryani Nuryani; Nanang Wiyono; Mohtar Yunianto; Budi Purnama; Utari Utari; Riyatun Riyatun; Suharno Suharno; Dwi Teguh Raharjo (Department of Physics, Sebelas Maret University, 2022)
An android-based fetal heart rate measurement is presented in this article. The fetal heart rate was obtained from the mother's abdominal electrocardiogram which was then measured and processed by Raspberry pi using k-means. Raspberry pi processed results produce ECG signals and fetal heart rate which was displayed on Android devices in real-time. The android application can also save heart rate and ECG data or retrieve previously taken heart rate recordings. The system obtained that the average value of accuracy, sensitivity and predictive positive were 90.49%, 97.10% and 93.03%, respectively. The variation of the training time of the algorithm showed that the training time of 10 and 15 seconds mostly has better performance than the training time of 5 seconds.